2000
DOI: 10.1002/1097-4547(20001101)62:3<319::aid-jnr1>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor and basic fibroblast growth factor regulate cell proliferation and the expression of notch-1 receptor in a new oligodendrocyte cell line

Abstract: We generated a new cell line, N38, by conditionally immortalizing mouse oligodendrocytes (OLs) at early stages of maturation. The morphology and marker expression pattern suggest N38 cells are similar to immature OLs. N38 cells were sensitive to changes in serum concentrations, and forcing the cells to differentiate in low serum at 39°C significantly decreased the survival of the cells. Importantly, addition of PDGFaa, bFGF or astrocyte‐conditioned medium had protective effects on the cells, by increasing cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…It was reported that PDGF signaling regulates the expression of Notch-1 receptor in other cell lines (20). Notch-1 signaling is known to play important roles in maintaining the balance between cell proliferation, differentiation, and apoptosis (26).…”
Section: Down-regulation Of Pdgf-d Inhibits Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that PDGF signaling regulates the expression of Notch-1 receptor in other cell lines (20). Notch-1 signaling is known to play important roles in maintaining the balance between cell proliferation, differentiation, and apoptosis (26).…”
Section: Down-regulation Of Pdgf-d Inhibits Angiogenesismentioning
confidence: 99%
“…It has been reported that Notch-1 is critically involved in the processes of tumor cell proliferation and apoptosis (19). PDGF-A has been shown to activate the expression of Notch-1 in certain cell lines (20). Therefore, we investigated whether Notch-1 was down-regulated by PDGF-D siRNA in pancreatic cancer cell lines.…”
Section: Cancer Researchmentioning
confidence: 99%
“…This reduction did not require FGF2 treatment and was not altered by expression of FGFRdn to disrupt FGFR signaling. Therefore, although FGF2 has been shown to increase Notch1 expression [4,5], Notch1 expression may already be sufficient so that FGF2 treatment does not regulate Jagged1 inhibition of OP differentiation in this context. Conversely, FGF2 treatment markedly reduced O1 acquisition among GFP+ cells in OP cell cultures or among OP cells co-cultured with Jagged1-expressing fibroblasts (Figure 1 D, b and c; 1 E).…”
Section: Resultsmentioning
confidence: 95%
“…FGF2 can induce Notch1 expression in neuroepithelial precursor cells and in a cell line with an immature oligodendrocyte phenotype [4,5]. Conversely, Notch1 signaling can increase responsiveness to FGF2 in telecephalic progenitors [24].…”
Section: Introductionmentioning
confidence: 99%
“…The surviving mice develop a number of defects including oligodendrocyte deficiency, lack of alveolar smooth muscle cells, lack of testicular leydig cells and a disturbance of intestinal villus formation (Betsholtz et al 2001). In an oligodendroglial cell line the treatment of cells with PDGFAA resulted in the increased expression and polarization of the notch-1 receptor (Bongarzone et al 2000), which is important in maintaining cells in an undifferentiated state (Lardelli et al 1995, Simpson 1998. Therefore, it is likely that cross-talk between PDGFAA and the notch signaling pathways maintain the pancreatic progenitor cells in an undifferentiated state, allowing regeneration in the adult.…”
Section: Discussionmentioning
confidence: 99%